Peranan Kreativitas dan Inovasi dalam Peningkatan Produktivitas UMKM Pengolah Mangga Podang (Studi pada Kelompok Tani Wanita â€œBudidayaâ€ Desa Tiron Kecamatan Banyakan Kabupaten Kediri) - Purwaning Diah, Martina (Jurnal Ilmiah Administrasi Publik, 2019)
Kediri Regency is a podang mango center in East Java. Tiron village located on the slopes of Wilis mountain is one of the largest areas of podang mango. It was utilized by local communities to make fresh podang mango into products that have high economic selling value. The womenâ€™s farmer group "Budidaya" is one ofÂ  the pioneers who start up the podang mango processing business which received the assistance from Japan International Cooperation Agency, Faculty of Agriculture Technology Universitas Brawijaya and Kediri Regency Local Government. This research was conducted to use the qualitative descriptive approach with data retrieval technique through the observation, interview and documentation. The results revealed that the lack of creativity and innovation fromÂ  the womenâ€™s farmer group â€œBudidayaâ€ makes the business run decline. It was also supported by the lack insight of the leader in developing business management so the business was to be bankrupt. The support of stakeholders were needed to develop the womenâ€™s farmer groupâ€œBudidayaâ€ increase the productivity and raise the high income. Moreover, the product could be one of best product from Kediri Regency.